Biochemical assessment of uric acid and magnesium in prediabetic patients in Peshawar-KP: A case-control study. - Shah , Farid Ullah; Naeem , Awais; Naim , Fahad; Ahmad , Wasim (International Journal of Endorsing Health Science Research, 2022)
Background: Background: There is a lack of information regarding serum uric acid (SUA) and magnesium levels among the pre-diabetics population. This study aimed to assess the biochemical assessment of both uric acid and magnesium in prediabetics of the Peshawar-KP region. Methodology: In this case-control study, patients having normal glucose levels were considered as control, and prediabetics were cases. Fasting blood glucose (FPG) levels between 100-125 mg/dl or HbA1c levels between 5.7 to 6.4% were considered pre-diabetic. SUA was assessed by the Uricase method, serum Mg+ by the Calmagite calorimetric method, and fasting glucose was assessed by the GOD-POD enzymatic method. Results: According to our findings, mean values of serum magnesium were 2.12 ± 0.60 mg/dl (p=0.026) and 1.10 ± 0.82 mg/dl (p=0.001) in male and female of control group whereas, 1.60 ± 0.44 mg/dl (p=0.004) and 0.90 ± 0.22 mg/dl (p=0.002) in male and female of cases group respectively. Correspondingly, mean value of SUA was recorded as 4.14 ± 0.66 mg/dl (p=0.008) and 3.12 ± 0.38 mg/dl (p=0.004) in male and female of control group whereas 8.10 ± 1.00 mg/dl (p=0.002) and 6.22 ± 0.44 mg/dl (p=0.003) in male and female of cases and subjects group respectively. It is noticeable that mean serum magnesium and SUA values were higher in the male of both groups compared to females. Conclusion: The study concluded that lower serum magnesium levels in prediabetics might result from the closure of K+ channels, defective phosphorylation of insulin receptors, or diminished glucokinase activity. Higher uric acid levels in prediabetics might result from inflammation, oxidative stress, and hypertrophy of the tubules.